2005
DOI: 10.4049/jimmunol.175.3.2000
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fibroblast-Derived IL-10 Increases Survival of Mucosal T Cells by Inhibiting Growth Factor Deprivation- and Fas-Mediated Apoptosis

Abstract: Mucosal T cells are essential to immune tolerance in the intestine, an organ constantly exposed to large amounts of dietary and bacterial Ags. We investigated whether local fibroblasts affect mucosal T cell survival, which is critical for maintenance of immune tolerance. Coculture with autologous fibroblasts significantly increased viability of mucosal T cells by inhibiting IL-2 deprivation- and Fas-mediated apoptosis, an effect that was both contact- and secreted product-dependent. Investigation of antiapopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…In addition, we demonstrate in this study that IL-10 was not only produced, but also secreted, in the culture medium of mucosa explant cultures. The current prevailing concept in the literature is that IL-10 is synthesized in the human intestinal mucosa mainly by immune cellsincluding regulatory T cells, B cells, macrophages, and dendritic cells -and also by fibroblasts and epithelial cells (15,(20)(21)(22), a distribution analog to that previously reported in the mouse intestinal mucosa (23)(24)(25)(26)(27)(28)(29). Here we show that IL-10 was constitutively synthesized and secreted in the human colonic mucosa by resident cells, including epithelial cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In addition, we demonstrate in this study that IL-10 was not only produced, but also secreted, in the culture medium of mucosa explant cultures. The current prevailing concept in the literature is that IL-10 is synthesized in the human intestinal mucosa mainly by immune cellsincluding regulatory T cells, B cells, macrophages, and dendritic cells -and also by fibroblasts and epithelial cells (15,(20)(21)(22), a distribution analog to that previously reported in the mouse intestinal mucosa (23)(24)(25)(26)(27)(28)(29). Here we show that IL-10 was constitutively synthesized and secreted in the human colonic mucosa by resident cells, including epithelial cells.…”
Section: Discussionmentioning
confidence: 48%
“…It is inappropriate to infer the mucosal effect of IL-10 produced in situ from experiments based on systemic administration. This issue has already been raised by Ina et al (15), who showed, in a coculture model system, the importance of studying organ-specific cells to define the mechanisms of intestinal mucosa homeostasis.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, mesangial cells and mesenchymal cells may contribute to the IL-10 production [156,157]. Thus, it is plausible that IL-10 influences the local microenvironment through tissue-specific regulatory mechanisms.…”
Section: Production Of Il-10 By Parenchymal Cells and Tissue Imprintingmentioning
confidence: 99%
“…Intestinal myofibroblasts furthermore seem to be able to influence the rate of apoptosis of immune cells [46][47][48]. Thereby they might influence the balance between different T-cell subsets which could be another important influence factor on inflammation and the mucosal immune system.…”
Section: Recent Finding Further Indicate That Intestinal Fibroblasts mentioning
confidence: 99%